2012
DOI: 10.1371/journal.ppat.1002782
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Prion Transmission by Blood Transfusion

Abstract: It is now clearly established that the transfusion of blood from variant CJD (v-CJD) infected individuals can transmit the disease. Since the number of asymptomatic infected donors remains unresolved, inter-individual v-CJD transmission through blood and blood derived products is a major public health concern. Current risk assessments for transmission of v-CJD by blood and blood derived products by transfusion rely on infectious titers measured in rodent models of Transmissible Spongiform Encephalopathies (TSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
83
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 35 publications
8
83
2
2
Order By: Relevance
“…These experimental transfusion studies have confirmed that all blood fractions prepared by protocols similar to those used in transfusion medicine can transmit prion disease [23,24]. In addition, prion transmission by transfusion of cellular blood fractions was not solely dependent on their infectious titre since prion disease was more efficiently transmitted with viable rather than non-viable leukocytes [20]. While these studies have collectively been immensely informative in providing evidence that blood from prion-diseased hosts can harbour prion infectivity, the bioassays used to establish this are relatively cumbersome and time-consuming.…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…These experimental transfusion studies have confirmed that all blood fractions prepared by protocols similar to those used in transfusion medicine can transmit prion disease [23,24]. In addition, prion transmission by transfusion of cellular blood fractions was not solely dependent on their infectious titre since prion disease was more efficiently transmitted with viable rather than non-viable leukocytes [20]. While these studies have collectively been immensely informative in providing evidence that blood from prion-diseased hosts can harbour prion infectivity, the bioassays used to establish this are relatively cumbersome and time-consuming.…”
Section: Introductionmentioning
confidence: 60%
“…Our studies here support the view that the level of prion infectivity in blood from prion-diseased individuals may be underestimated when assessed by intracerebral inoculation of rodents in comparison with bioassay of similar material in other experimental systems. This is particularly pertinent to our assessment here of prion-infected plasma that could be diluted by several orders of magnitude and still trigger a phenotypic response in the PrP transgenic Drosophila, but appears to contain a low level of infectivity when assayed in other systems [10,[15][16][17][18][19][20][21]. One possibility for the efficient detection of scrapie-infected sheep plasma by PrP transgenic Drosophila is that this invertebrate host does not normally express PrP and may therefore not have evolved suitable defence mechanisms that efficiently remove or sequester misfolded neurotoxic forms of this protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations